ГИГАНТОКРИСТАЛЛИЧЕСКИЙ ХЛОРИТОИД ПРИПОЛЯРНОГО УРАЛА - Козырева И.В.; Швецова И.В.; Юдович Я.Э. (My University, 2005)
Unique vien-shaped occurrences of the giant-crystal chloritoid, with pyrophyllite and hematite, have been discovered in 1996 in glacier cirque of the Grubependity lake on the Maldynyrd ridge (the Near-Polar Urals), within zone of the Later Paleozoic Ozerny fault inheriting the ancient Maldinsky lineament. There are two varie-ties of the segregations: the pegmatoid-like ones, formed by coarse and giant chloritoid crystals (up to 10 cm in size), and, secondly, aggregates of the fine-grained chloritoid. There were detected three morphological varieties of the mineral: 1) aggregates of fine-lamella, flaky chloritoid crystals; 2) idiomorphic thick- and thin-tabular translucent crystals sometimes with pseudohexagonal appearance; 3) spherulite-like aggregations of radial-co-lumnar intergrowths of chloritoid crystals. Chemical composition of chloritoid corresponds to the standard one, with some enrichment in Mn. Amount of accessory minerals in chloritoid segregations makes 1-2 % of the hea-vy fraction. They include native gold, pyrite, chalcopyrite, leucoxene, rutile, diaspore, barite, monazite, xenotime, zircon, euclase, tourmaline, piedmontite, Mn-allanite, ardennite, spessartine, florencite. Among new fin-dings there are cervandonite and thalenite. Due to micro-inclusions of accessory REE-minerals (monazite, xenotime, florencite, and allanite) chloritoid aggregates are enriched in REE, up to 5500 ppm, though the chloritoid itself is REE-free. Origin of the aggregates (chloritoid, pyrofyllite, hematite) seems to be connected with leac-hing of Fe, Al, REE, etc. from the host schists (€3-O1) by the low-temperature hydrothermal solutions during the Late Paleozoic tectonic activation.
Keywords: 550.4:552.5(470.13)